State and Trends of the Carbon Market 2011 - Linacre, Nicholas; Kossoy, Alexandre; Ambrosi, Philippe (World Bank, Washington, DC, 2013)
After five consecutive years of robust growth, the total value of the global carbon market stalled at $142 billion. Suffering from the lack of post-2012 regulatory clarity, the value of the primary Clean Development Mechanism (CDM) market fell by double-digits for the third year in a row, ending lower than it was in 2005, the first year of the Kyoto protocol. The Assigned Amount Unit (AAU) and the United States Regional Greenhouse Gas Initiative (RGGI) markets shrank as well. As these segments declined, the dominance of the European Union Allowances (EUAs) market became more pronounced than ever and the share of the carbon market primarily driven by the EU Emissions Trading Scheme (EU ETS) rose to 97 percent, dwarfing the remaining segments of the market. The carbon market growth halted at a particularly inopportune time: 2010 proved to be the hottest on record, while emission levels continued their seemingly inexorable rise. In the end, however, the year may be remembered most for the political opportunities that arose, yet were ultimately failed to materialize in the United States, Japan, Australia, and the Republic of Korea. While the international regulatory environment remains uncertain, national and local initiatives have noticeably picked up and may offer the potential to collectively overcome the international regulatory gap. These initiatives signal that, one way or another, solutions that address the climate challenge will emerge.